Alianças desveladas : o silenciamento dos cuidados paliativos em uma clínica oncológica - Mendes, Camila Nunes (2024)
The practice of palliative care in an oncology clinic requires clear communication about prognosis, a challenge often observed in its implementation. With this in mind, the research aimed to understand, from a psychoanalytic perspective, the positioning of the medical team in an oncology clinic regarding prognosis information, its impact on healthcare practices, and its influence on how patients and their families process this information. The methodology of this investigation examines not only the explicit statements of the institution's actors but also uncovers hidden meanings that the researcher can interpret. Thus, a psychoanalytic researcher embedded in the investigation field is essential to access the full range of possible data and explore unexpected findings. Data collection included field diaries and semi-structured interviews with the medical team, other healthcare staff, patients, and family members, and the resulting information was analyzed in light of the study objectives within the research group Só Depois. Interestingly, findings during the research process indicated that the health team’s challenge with palliative care was not directly linked to the medical team’s approach to prognosis communication, as initially hypothesized. Instead, the results revealed that the various participants in the institution formed an unconscious alliance that silenced, or perhaps obstructed, the practice of palliative care.